Policy Reforms Augmenting Farm-to-Fork-Links in Fisheries of West Bengal, India - Suman Dey; S.N. Ojha (Journal of Indian Fisheries Association, 2018)
Among all the states in India, West Bengal, ranks second in total fish production. However, the state is notable to meet the increasing demand of fish. Therefore, it was found to be necessary to explore the status of fisheries resources and analyze the factors of production. Accordingly, this study was conducted to gain an understanding of the existing status of fisheries, resource galore, organizational structure and administration of the government organizations working for the fisheries sector of West Bengal and the factors affecting fish production in the state using the secondary data available from the Department of Fisheries, Govt of West Bengal Correlation matrix using SPS5 was formed to see the level of association among the various factors and stepwise multiple regression analysis was done using SPS to find out the independent variables that significantly affect the dependent variables. The results of the study depicted that vast untapped natural fisheries resources are available in the state which needs to be utilized. In the study, the fish production was found to be significantly correlated with the increase in the water area under fish culture and the ’increase in the domestic demand of fish in the state, Henceforth, the government should focus in these two factors along with other important factors for increasing the production in the near future.